PENDAMPINGAN GURU MADRASAH DINIYAH DALAM PENGEMBANGAN MEDIA PEMBELAJARAN EDUKATIF BERBASIS RODA ANGKA DAN KINCIR SHOROF - Mukaromah, Ning; Suadi, Suadi (INAIFAS Press, 2025)
Education plays a crucial role in shaping individual character and quality. However, limitations in funding and supporting facilities make it challenging to provide diverse and innovative learning media. This situation results in a conventional learning process that is less engaging for students. The aim of this community service program is to enhance the pedagogical competence of Madrasah Diniyah teachers in developing creative, contextual, and easily implementable educational media based on Roda Angka and Kincir Shorof. The methods employed include initial observation, guided practice in media creation, and evaluation of training outcomes. The results indicate a significant improvement in teachers’ understanding and skills in developing educational media. Teachers are able to create simple yet effective learning media that increase student engagement and motivation. In addition, the program successfully established a community of creative Madrasah Diniyah teachers, serving as a platform for ongoing collaboration and innovation. In conclusion, this practice-based teacher mentoring program has proven effective in promoting learning transformation in nonformal educational institutions and can serve as a model for professional development of teachers in other Madrasah Diniyah